Nursing Interventions in Mental Health: Impact on Patient Recovery, Relapse Prevention, and Quality of Life - Wazzan, Naif Ahmed; Alzaidi, Fahad Saeed; Faqeeh, Mazen Ali Al; Shahan, Zainab Ahmed; Habiballah, Esraa Talal; Alshekhe, Ibrahim Mohameed; Almalalwi, Faisal Sulayyih Kaliaf; Al-Thaqafi, Fahd Saud Attia; Alzahrani, Salman Saad Mohammed; Alaltwai, Mohammed Odah Slamh (Journal of Posthumanism, 2024)
Mental health disorders are a leading cause of disability worldwide, with increasing prevalence and long-term impacts on individuals, families, and healthcare systems. Nursing interventions play a vital role in promoting recovery, preventing relapse, and improving the overall quality of life for patients with psychiatric conditions. This article systematically examines the effectiveness of nursing interventions across various mental health settings, including inpatient, outpatient, and community-based care. It highlights key strategies such as therapeutic communication, medication adherence support, psychosocial interventions, crisis management, and family involvement. The review synthesizes current evidence indicating that mental health nurses significantly contribute to symptom stabilization, reduction of hospital readmissions, and enhancement of patient autonomy. Furthermore, the article explores how nursing interventions align with holistic and recovery-oriented models, addressing biological, psychological, and social determinants of health. The analysis underscores the importance of early identification of relapse indicators, patient-centered care planning, and continuous monitoring, which are instrumental in sustaining long-term recovery outcomes. The findings suggest that empowering mental health nurses through training, policy support, and integration of digital technologies can further strengthen their impact. Ultimately, this review emphasizes that nursing interventions are not merely supportive but are central to effective psychiatric care, driving measurable improvements in patient outcomes and quality of life